Interactional validity: assessing technologies to support embodied activities - Luff, P; Jirotka, M; Yamashita, N; Kuzuoka, H; de la Flor, G; Heath, C (2011)
In this brief paper we discuss how we may draw upon workplace studies to inform the ways we assess innovative technologies to support embodied interaction. In particular, we discuss the challenges of designing quasi-naturalistic experiments to assess systems to support distributed embodied interaction.